2007
DOI: 10.1111/j.1365-2966.2006.11299.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsation-decline relationships in R Coronae Borealis stars

Abstract: Decline onset times were measured in long‐term visual light curves for five R Coronae Borealis (RCB) variable stars. These included RY Sgr and V854 Cen, the two RCB stars previously reported to have a relationship between dust formation events and pulsational variations. Analysis of the decline epochs showed that all decline onsets for a given star obey a linear ephemeris tied to the object's dominant radial pulsation period. Thus, in addition to confirming the pulsation–decline correlation for RY Sgr and V854… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The onset of dust formation has been found to be correlated with the pulsational phase in five RCB stars, including RY Sgr and V854 Cen (Pugach 1977; Lawson et al 1999; Crause et al 2007). RCB stars’ pulsation amplitudes are at most a few tenths of a magnitude and their periods are 40–100 d (Lawson et al 1990; Lawson & Cottrell 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of dust formation has been found to be correlated with the pulsational phase in five RCB stars, including RY Sgr and V854 Cen (Pugach 1977; Lawson et al 1999; Crause et al 2007). RCB stars’ pulsation amplitudes are at most a few tenths of a magnitude and their periods are 40–100 d (Lawson et al 1990; Lawson & Cottrell 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of traditional (i.e., trigonometric) methods of estimating luminosity, we rely on the pulsation-period relation for RCBs. Pulsation is also of direct interest to the puzzle of dust formation in that a link, first suggested by Pugach (1977) and confirmed by Crause et al (2007) ties onset of dust formation to a preferred phase in a RCBs radial pulsation. However, copious dust formation appears not to occur at every passage through the preferred phase.…”
Section: Dust and Luminositymentioning
confidence: 90%
“…and other stars [4], it has been found that a global light minimum begins after a pulsation light maximum in an interval of pulsation phase of 0.2-0.4. For RY Sgr and FG Sge it has also been found that the end of a minimum is also related to the pulsations:…”
Section: Discussionmentioning
confidence: 99%
“…Condensation of dust along the line of sight is recognized as the cause of the decline in brightness. Observations have shown that the condensation process is associated with pulsations of the star [3,4]. The leading role of pulsations in the global variability of the star has stimulated research on the effect of pulsations on the parameters of the star's atmosphere.…”
Section: Introductionmentioning
confidence: 99%